Cone beam CT verification for oesophageal cancer - impact of volume selected for image registration. - Hawkins, M; Aitken, A; Hansen, V; McNair, H; Tait, D (2011)
PURPOSE: Oesophageal cancers are difficult to visualise on volumetric imaging and reliable surrogate are needed for accurate tumour registration. The aim of this investigation is to evaluate the effect of a user defined volume with automated registration techniques using commercially available software with the on-board volumetric imaging for treatment verification of oesophageal cancer and determine the optimum location of this volume. MATERIAL AND METHODS: In 20 patients four 'clipbox'(C) volumes were defined: C-planning target volume (PTV), C-carina, C-vertebrae, C-thorax. The set-up corrections (translational and rotational) for C-PTV were compared to the corrections using C-carina, C-vertebrae and C-thorax. RESULTS: Six hundred and eight registrations were performed. The best concordance in set-up corrections was found in the superior/inferior direction between C-PTV and C-carina (76%). In the right/left and anterior/posterior direction, better agreement was found between C-PTV and C-thorax with 80% and 76% agreement, respectively. Automatic 'bone' registration using C-vertebrae failed in 28% of scans. The correlation ratio between C-PTV and C-carina (n = 4) for mid-oesophageal tumours was 0.88, 0.79, and 0.95 in the right/left, superior/inferior and anterior/posterior directions, respectively. CONCLUSION: The defined volume for matching is important for oesophageal tumours. The alignment 'clipbox' and registration method selected can affect the displacements obtained. This may best be determined by tumour location and highlights the need to diversify protocols within one tumour treatment site. Further analysis is required to validate carina as a tumour surrogate for mid-oesophageal tumours.